PENGARUH KINERJA MANAJEMEN MUTU, MANAJEMEN PEMASARAN DAN AUDIT INTERNAL TERHADAP AKREDITASI PELAYANAN RUMAH SAKIT SWASTA DI PEKAN BARU - Erfan Effendi (JURNAL KOMPETITIF, 2018)
Knowledge of hospital quality programs in Indonesia has many beneficial effects for patients and service providers. Improved quality has made perceptions about hospital services better in the patient's view, which in turn has resulted in increasing the use of hospital services so that the income received by hospitals is increasing. Hospital Accreditation in Indonesia is carried out to assess hospital compliance with accreditation standards. Hospital accreditation that has been implemented since 1995 in Indonesia, so far uses accreditation standards based on what year the standard began to be used for assessment, so far there has never been a National Accreditation of Hospitals in Indonesia, while the accreditation status currently has national and international accreditation status. The National Hospital Accreditation Standards that are valid in 2018 include: patient safety goals, patient-focused goals, hospital management standards, and implementation of national programs, as well as integration of health education in hospital services.This study was aimed at investigating the effect of quality management, marketing management and internal auditing on private hospital service accreditation, taking a sample of 26 accredited private hospitals in Palembang and Pekanbaru by the Hospital Accreditation Commission (HAC). Data analysis was used to test hypotheses using Multiple Linear Regression analysis. The results of this study concluded that accreditation of private hospital services in Pekanbaru was good, the level of compliance from the management of private hospitals in Pekanbaru was higher, because of the 26 hospitals 61.5% were accredited by HAC. Key words: quality management, marketing management, internal audit and hospital service accreditation.